Phytochemical Screening, antioxidant activity, and Mineral Profiling of Rosmarinus Officinalis L. from Msallata Region (Libya) - Elsherif, Khaled Muftah; Alhlbad, Ebtesam Abdallah Ahmed; Ewlad-Ahmed, Abdunaser Mabrok (Scientific Journal for Faculty of Science-Sirte University, 2023)
The aim of this study was to investigate the phytochemical constituents, total phenols, total antioxidant, and mineral contents of Rosmarinus Officinalis L. The aerial parts of the plant were extracted using different solvents, including water, ethanol, ethyl acetate, and chloroform. The extracts were analyzed for their phytochemical constituents. The total phenolic content and total antioxidant capacity were measured using colorimetric assays. The mineral content of the plant was analyzed using AAS. The results showed that the plant extracts were rich in carbohydrates, proteins, phenols, alkaloids, flavonoids, tannins, glycosides, and coumarins. The total phenolic content of the plant extracts ranged from 76.7 to 95.5 mg GAE/g, indicating strong antioxidant activity, with a total antioxidant capacity of 50.03 mg/g. The plant was found to be rich in macro elements such as Na, K, Ca, Mg, and P, with concentrations ranging from 1760 to 12155 mg/kg. The water extract contained fewer phytochemical constituents compared to the ethanolic extract, while the ethyl acetate and chloroform extracts showed the presence of only specific compounds. These findings suggest that Rosmarinus Officinalis L. is a valuable natural source of bioactive compounds and essential nutrients. Further research is needed to fully elucidate the therapeutic properties of the plant and to explore its potential use in the prevention and treatment of various diseases.